2002
DOI: 10.1007/s198-002-8338-8
|View full text |Cite
|
Sign up to set email alerts
|

German Pediatric Reference Data for Quantitative Transverse Transmission Ultrasound of Finger Phalanges

Abstract: Quantitative ultrasound (QUS) of the finger phalanges is a useful tool in the assessment of disease- or age-related deterioration of bone. For studying the impact of juvenile diseases or growth disorders affecting the skeleton, a reference database for QUS parameters is needed. The aim of this study was to establish a calibrated reference database of parameters of transverse ultrasound transmission through juvenile finger phalanges. A total of 1328 children (650 females, 678 males; ages 3-17 years) were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
2
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 12 publications
4
45
2
7
Order By: Relevance
“…These anthropometric factors could be responsible for the bet- ter bone status assessed by QUS. There was no correlation between Ad-SoS and BMI or body mass in the girls from our study, contrary to other studies [4][5][6]. Physical fitness could influence Ad-SoS in our group, since a statistically significant positive correlation between them was shown.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These anthropometric factors could be responsible for the bet- ter bone status assessed by QUS. There was no correlation between Ad-SoS and BMI or body mass in the girls from our study, contrary to other studies [4][5][6]. Physical fitness could influence Ad-SoS in our group, since a statistically significant positive correlation between them was shown.…”
Section: Discussioncontrasting
confidence: 99%
“…This is influenced by a number of factors like body mass, sexual development, physical fitness and environmental factors [2,5,6,18]. The impact of the place of residence could influence physical development, since the girls from our study group had generally higher weight, height and BMI than the controls.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was calculated by means of a standard Z-score transformation using mean value and standard deviation appropriate for age and sex groups. Normative data for phalangeal quantitative ultrasound variables were published [12,16,18,19]. The coefficient of variation (CV%) for QUS measurements was 0.64%.…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…Other authors reported that the difference in QUS parameters between genders become significant in older age groups, particularly at puberty (Baroncelli et al, 2001;Barkmann et al, 2002).…”
Section: Discussionmentioning
confidence: 96%